Assessment of symptom improvement following nasal septoplasty with or without turbinectomy - Velasco,Leandro Castro (2011)
Most studies show that objective measures to quantify and determine surgical success in the treatment of nasal obstruction do not correlate with subjective improvement as reported by patients. AIM: To evaluate the subjective improvement of nasal symptoms in patients undergoing septoplasty with or without turbinectomy. MATERIALS AND METHODS: A prospective study. We evaluated 72 septoplasty patients with or without partial inferior turbinectomy; the patients answered a questionnaire preoperatively and on the 60th day after surgery. RESULTS: Septoplasty was done associated with bilateral partial inferior turbinectomy in 83.3% of patients; it was unilateral in 9.7%; there was no need for turbinate reduction in 6.9%. An improvement of all symptoms was observed after surgery. Nasal obstruction had improved in 68 patients (94.4%) by the 60th postoperative day. The average nasal obstruction score in patients with and without allergic symptoms was similar before surgery and on the 60th postoperative day. Older patients had milder preoperative allergic symptoms. CONCLUSIONS: Nasal symptoms in patients undergoing septoplasty, with or without turbinectomy, improved. Patients with and without allergic symptoms showed a similar improvement of nasal obstruction on the 60th postoperative day.